Management of desmoid-type fibromatosis involving peripheral nerves - Mario G. Siqueira; Paulo L. Tavares; Roberto S. Martins; Carlos O. Heise; Luciano H.L. Foroni; Marcelo Bordalo; Roberto Falzoni (Arquivos de Neuro-Psiquiatria)
Desmoid-type fibromatosis is an uncommon and aggressive neoplasia, associated with a high rate of recurrence. It is characterized by an infiltrative but benign fibroblastic proliferation occurring within the deep soft tissues. There is no consensus about the treatment of those tumors. We present a surgical series of four cases, involving the brachial plexus (two cases), the median nerve and the medial brachial cutaneous nerve. Except for the last case, they were submitted to multiple surgical procedures and showed repeated recurrences. The diagnosis, the different ways of treatment and the prognosis of these tumoral lesions are discussed. Our results support the indication of radical surgery followed by radiotherapy as probably one of the best ways to treat those controversial lesions.